How empathy styles mediate the relationship between responsive parenting and adolescent friendship quality? - Mahirah, Aaliya Hana; Muttaqin, Darmawan (Psychological Research on Urban Society, 2022)
Responsive parenting contributes to the friendship quality formed in adolescents. Previous studies failed to fully explain the relationship process between responsive parenting and friendship quality. Empathy is one of the interpersonal skills formed through responsive parenting. Therefore, this study aims to examine the role of empathy in responsive parenting relations with friendship quality. A total of 450 respondents, including the early, middle, and late adolescents aged 12-15, 15-18, and 18-20 years, were selected as participants. Responsive parenting, empathy style, and friendship quality was measured using the Parental Responsiveness Scale, Interpersonal Reactivity Index, and the McGill Friendship Questionnaires-Friend's Functions. The research data were analyzed using regression analysis and Sobel test. The results showed that empathy is a mediator in the relationship between responsive parenting and friendship quality. Also, responsive parenting does not directly predict friendship quality but first develops fantasy and personal stress styles. Adolescents with high personal distress show sensitivity to the feelings and thoughts of their friends because the relationships formed are of higher quality.